2021
DOI: 10.1186/s12870-021-03316-8
|View full text |Cite
|
Sign up to set email alerts
|

Leaf functional traits differentiation in relation to covering materials of urban tree pits

Abstract: Background Understanding the ecological strategies of urban trees to the urban environment is crucial to the selection and management of urban trees. However, it is still unclear whether urban tree pit cover will affect plant functional traits. Here, we study the response of urban trees to different tree pit covers, analyzed the effects of different cover types on soil properties and their trade-off strategies based on leaf functional traits. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Environmental factors promote the optimization of functional strategies by expressing multiple traits, and eventually form a series of trait groups and respond to environmental changes synergistically [48,49]. In our research, the environment had a significant effect on the LW, SLA, LDMC, LCC, LNC, LPC, C/N, C/P, and N/P (p < 0.001), and significant effect on the LA (p < 0.01).…”
Section: The Adaptabilities Of Landscape Plants To the Different Gree...mentioning
confidence: 52%
“…Environmental factors promote the optimization of functional strategies by expressing multiple traits, and eventually form a series of trait groups and respond to environmental changes synergistically [48,49]. In our research, the environment had a significant effect on the LW, SLA, LDMC, LCC, LNC, LPC, C/N, C/P, and N/P (p < 0.001), and significant effect on the LA (p < 0.01).…”
Section: The Adaptabilities Of Landscape Plants To the Different Gree...mentioning
confidence: 52%
“…Plants adapt to changing external environments and meet actual physiological needs by coordinating changes in their functional traits [ 61 ]. Plants with lower stomatal density response to water loss can adapt to fluctuating environmental conditions [ 25 ]. We detected that street trees have lower stomatal density than the park and may have higher water use efficiency [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another group of leaf traits form leaf hydraulic traits, such as leaf hydraulic conductivity and leaf turgor loss point, which are related to plant hydraulic efficiency and safety under environmental stresses. Recent studies have demonstrated the presence of hydraulic degradation and leaf economic trait trade-offs for trees in urban pavement environments [ 16 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total P, K, Ca, Mg, Cu, Fe, Al, Zn, and Mn contents were determined by Optima 8 000 ICP-OES inductively coupled plasma emission spectrometer (PerkinElmer, USA) [ 73 ]. Soil pH was measured by potentiometric method [ 74 ], soil moisture content (SMC), moisture holding capacity and saturated water content were measured by drying method [ 75 ], and soil bulk density, total soil porosity, capillary porosity, and non-capillary porosity were measured by ring-knife method [ 76 ].…”
Section: Methodsmentioning
confidence: 99%